Prophetic Leadership Mahasiswa: Studi pada Program Pembentukan Kepribadian dan Kepemimpinan Universitas Muhammadiyah Malang - Aliya Izzet; Tobroni Tobroni; Abdul Hari; Dina Mardiana (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2020)
The decline of national leadership integrity in recent years is something that we should underline and must be addressed. So that the younger generation does not follow a bad example from existing leaders. As a Muslim, we have an exemplary figure who is always a good role model in speaking, acting and holding a strong principle of life. He was the Prophet Muhammad who had great leadership and what we know as the term Prophetic Leadership.The aim of this study was to find out how the concept of prophetic leadership developed in P2KK and its implementation in forming student prophetic leadership at University of Muhammadiyah Malang. This research was conducted at the UPT. P2KK University of Muhammadiyah Malang in May to June 2019. The approach used is explorative case study research. From the results of the study it was found that there were several concepts of prophetic leadership developed in P2KK, including Aqidah (faith) that was strong, trustworthy and responsible, fair, firmness, noble character , deliberation and proactive. While the implementation is done through simulations, discussions and activities outside the other classes (outbound) which are indirectly able to form the prophetic leadership of the students of the University of Muhammadiyah Malang.